Fluoroferrates with (dabcoH2)2+ or (dabcoH)+ Cations1. Issue 7 (13th February 2014) - Darmograi, Ganna; Jouffret, Laurent; Hémon‐Ribaud, Annie; Leblanc, Marc; Dujardin, Gilles; Maisonneuve, Vincent; Lhoste, Jerome
Abstract Four new hybrid fluoroferrates synthesized with 1, 4‐diazabicyclooctane (dabco) are discussed. They were obtained through the use of conventional solvothermal synthesis in Teflon vessels to explore the composition space diagram of the (Fe2+, Fe3+)‐dabco‐HFaq. chemical system with ethanol or dimethylformamide as solvent. These Class I hybrid fluorides exhibit isolated hydrated and/or fluorinated iron entities associated to mono or diprotonated amines according to the synthesis conditions. Their structures were determined from single crystal diffraction: (dabcoH2)[FeIII2F8(H2O)2] (I), triclinic, space group P<alternatives> <![CDATA[$\bar{1}$]]> <inline-graphic xlink:href="ark:/27927/pghmj32rc1" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>, Z = 2, a = 7.1657(2) Å, b = 7.6031(2) Å, c = 13.1497(3) Å, α = 73.631(1)°, β = 76.210(1)°, γ = 84.286(1)°, V = 667.1(1) Å3, R = 0.0299; (dabcoH2)2[FeIII2F10]·2H2O (II), orthorhombic, space group Pbca, Z = 4, a = 12.9801(7) Å, b = 11.4624(6) Å, c = 13.8641(7) Å, V = 2062.7(2) Å3, R = 0.0425; (dabcoH)4[FeIII2F10]·10H2O (III), triclinic, space group P<alternatives> <![CDATA[$\bar{1}$]]> <inline-graphic xlink:href="ark:/27927/pghmj32rbh" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>, Z = 1, a = 8.921(3) Å, b = 9.468(4) Å, c = 13.452(4) Å, α = 76.87(2)°, β = 74.62(2)°, γ = 74.86(2)°, V = 1042.2(6) Å3, R = 0.0549; (dabcoH)[(FeII(H2O)6)(FeIIIF6)] (IV), trigonal, space group P31c, Z = 2, a = 9.2866(2) Å, c = 10.2401(2) Å, V = 764.8(3) Å3, R = 0.0252. The paper focuses on structural descriptions, environment of dabco cations or iron species, and hydrogen bonding modes in the light of literature examples.